2013
DOI: 10.5539/jfr.v2n2p128
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Mycotoxigenic Fungi in Concentrated Poultry Feed in Niger State, Nigeria

Abstract: In Nigeria, concentrated poultry feed is a vital component of animal production and health but there was no reliable mycogram in Niger state, Nigeria. As a result this study determined the incidence of mycotoxigenic fungi in both commercial and privately milled concentrated poultry feeds. A total of 100 poultry feed samples consisting of 52 privately milled poultry feed and 48 commercial feed samples were collected. Mycoflora in the feed was determined. Nine fungi genera were isolated. The most frequently isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In this study, the results of fungi isolated from moldy feed showed Aspergillus and Penicillum as the predominant fungi genera as also stated in the work of Ariyo et al, (2013). Mycological examination was carried out for 150 samples of fish rations by El-Boshy et al, (2008) and a total prevalence of Aspergillus flavus was observed to be 66.6%.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, the results of fungi isolated from moldy feed showed Aspergillus and Penicillum as the predominant fungi genera as also stated in the work of Ariyo et al, (2013). Mycological examination was carried out for 150 samples of fish rations by El-Boshy et al, (2008) and a total prevalence of Aspergillus flavus was observed to be 66.6%.…”
Section: Discussionsupporting
confidence: 70%
“…A great body of research on mycotoxins showed that 98% of the ingredients used in animal feed formulation are positive for AFs. Moreover, maize has been reported as a preferred substrate for fungal growth and mycotoxin production in comparison with soybean and wheat in poultry feed [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Other species that produce aflatoxins include Aspergillus pseudotamarii, Aspergillus rambelli, and Aspergillus pseudocealatus (Coppock et al, 2018). Analysis of poultry feed in Nigeria showed the presence of Aspergillus species in both private and commercial mills (Ariyo et al, 2013).…”
Section: Aflatoxinsmentioning
confidence: 99%